2009
DOI: 10.1007/s10773-009-0202-z
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Dynamics of Relativistic Particle

Vasily E. Tarasov

Abstract: Fractional dynamics of relativistic particle is discussed. Derivatives of fractional orders with respect to proper time describe long-term memory effects that correspond to intrinsic dissipative processes. Relativistic particle subjected to a non-potential four-force is considered as a nonholonomic system. The nonholonomic constraint in fourdimensional space-time represents the relativistic invariance by the equation for fourvelocity u μ u μ + c 2 = 0, where c is a speed of light in vacuum. In the general case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…We also note some other formulations of the non-Markovian quantum dynamics by using fractional calculus: the non-Markovian dynamics of OQS with time-dependent parameters [39,45], relativistic open classical systems [46], and quantum systems with memory [47].…”
Section: Introductionmentioning
confidence: 99%
“…We also note some other formulations of the non-Markovian quantum dynamics by using fractional calculus: the non-Markovian dynamics of OQS with time-dependent parameters [39,45], relativistic open classical systems [46], and quantum systems with memory [47].…”
Section: Introductionmentioning
confidence: 99%
“…487–520, [ 9 ]). Relativistic open classical systems [ 58 , 59 ] and quantum systems with memory [ 60 ]. Classical system with memory as open system [ 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…In [11], the mass spectroscopy of heavy mesons were investigated within the frame of conformable derivative searching for any ordering effect in their spectra that varies with the fractional order. In [12], the fractional dynamics of relativistic particles was studied, and it was found that fractional dynamics of such particles are described as non-Hamiltonian and dissipative. Possibility of being Hamiltonian system under some conditions was also presented.…”
Section: Introductionmentioning
confidence: 99%